2020
DOI: 10.1039/d0cp03350b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular growth upon ionization of van der Waals clusters containing HCCH and HCN is a pathway to prebiotic molecules

Abstract: The growth mechanisms of organic molecules in an ionizing environment such as the interstellar medium are not completely understood. Here we examine by means of ab initio molecular dynamics (AIMD)...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…To understand the intra-cluster ionization process at the molecular level, several studies performed ab-initio molecular dynamics (AIMD) simulations modeling different neutral cluster compositions. In agreement with experimental work, AIMD simulations have demonstrated that the molecular growth process occurs and that covalently bonded structures are formed [ 38 , 41 , 42 , 43 ]. It has been shown that, upon ionization, part of the cluster forms covalently bonded core structures, while the remaining molecules serve as spectators of the process.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…To understand the intra-cluster ionization process at the molecular level, several studies performed ab-initio molecular dynamics (AIMD) simulations modeling different neutral cluster compositions. In agreement with experimental work, AIMD simulations have demonstrated that the molecular growth process occurs and that covalently bonded structures are formed [ 38 , 41 , 42 , 43 ]. It has been shown that, upon ionization, part of the cluster forms covalently bonded core structures, while the remaining molecules serve as spectators of the process.…”
Section: Introductionsupporting
confidence: 76%
“…In the remaining ~2.7% of the trajectories, we observed the aggregation of four acetylene molecules to yield bonded C 8 H 8 + . While other cluster compositions (namely, mixed acetylene with HCN and cyanoacetylene) enable bonding between four units [ 41 , 43 ], C 8 H 8 + species were not obtained from the acetylene hexamers previously studied, clearly demonstrating that more than six acetylene units are required to observe aggregation beyond C 6 structures from a pure acetylene cluster [ 38 , 42 ]. Again, this emphasizes the role of the cluster environment not only in the stabilization of the products but also in their formation.…”
Section: Resultsmentioning
confidence: 99%
“…While the possibility of molecular formation upon ionization of van der Waals clusters (intracluster growth mechanism) has been demonstrated before (26,40,44), this paper forms a direct connection of such a mechanism with astronomical measurements. By applying the intracluster growth to acetylene and cyanoacetylene mixed clusters, we were able to successfully predict benzonitrile radical cation formation which was recently identified experimentally in TMC-1.…”
mentioning
confidence: 63%
“…Recently, using ab initio molecular dynamics (AIMD) to model ionization of small neutral acetylene clusters, the potential of this conversion mechanism for forming aromatic molecules has been demonstrated (26,40,44). This process can lead to molecular growth, whereby structures are formed on the C4 and C6 potential energy surfaces, among them the benzene cation (40).…”
mentioning
confidence: 99%
See 1 more Smart Citation